(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present research is to examine the internet addiction among university students. The objective of the study is to find out the level of internet addiction among under graduate students and Post graduate students. Based on the previous studies, a hypothesis was framed that there is a significant difference in internet addiction among under graduate and Post graduate students. The sample consists of 30 under graduate students and 30 Post graduate students, who were studying in Affiliated Colleges and Bangalore University situated in bengaluru. Students were administered a Dr. Kimberly S. Young’s Internet addiction test (1998) along with information schedule. The obtained data were analysed using ‘t’ test .The obtained result shows that there is a significant difference in internet addiction among Under graduate students and Post graduate students.